(untitled) (Strathmore Law Review, 2022)
Biometric identity systems have been adopted in the Global South, following the Global North’s lead. The greatest discrepancy, however, is the existence of legal frameworks that govern the use, storage and processing of the data collected. The Kenyan government’s roll-out of the Huduma Namba registration exercise in April 2019 with no existing data protection law in Kenya exemplifies this. Thereafter, Parliament passed the Data Protection Act. Unfortunately, parts of this law are not keen enough to protect personal data. Deviating from the requirement for personal data to be directly collected from the data subject, section 28(2)(c) of the referenced Act permits indirect collection of personal data from a source other than the data subject themselves. Relying on desk-based research and using the Huduma Namba exercise as a case study, this paper examines this permission and the imminent danger it poses to privacy of the personal data of Kenyans. Finding that section 28(2)(c) exposes personal data to the privacy violations of secondary use and exclusion threatens the right to privacy, this research suggests that the meta consent model as embraced by the healthcare sector emerges as a feasible solution. This model allows data subjects to determine their consent preferences i.e., how and when they wish their consent to be sought for further collection and use, at the point of primary collection of personal data. Additionally, this paper recommends that the model should be embraced by the judiciary in its adjudication of matters and finally, that an amendment incorporating the solution should be made.